Using Disability-Adjusted Life Years to Assess the Burden of Disease and Injury in Rhode Island - Jiang, Yongwen (Association of Schools of Public Health, 2012)
OBJECTIVES: Disability-adjusted life years (DALYs) measure the burden of disease and injury in a population. We tested the feasibility of calculating DALYs to assess the burden of disease and injury in Rhode Island (RI). METHODS: We computed DALYs for the 2008 RI population using methods developed by the World Health Organization, Harvard University, and the World Bank. DALYs are a composite measure that sum years of life lost (YLLs) due to premature mortality with years lived with disability (YLDs). We calculated crude mortality, YLLs, YLDs, and DALYs for 90 major health conditions for RI and stratified them by gender and age. Calculations for YLLs and YLDs were based on five-year averages. We compared our results with U.S. and Los Angeles County, California, estimates. RESULTS: A DALYs ranking produces a different picture of RI's disease and injury burden than does mortality-based ranking. Of 90 major health conditions assessed for RI, six of the top 10 causes for mortality and DALYs were the same, but were ranked differently: ischemic heart disease, cerebrovascular disease, Alzheimer dementia and other dementias, trachea/bronchus/lung cancer, chronic obstructive pulmonary disease, and diabetes mellitus. These six conditions accounted for 59% of deaths but only 35% of DALYs. Causes and rank orders for DALYs differed between males and females and among age groups. CONCLUSIONS: Including nonfatal health conditions in an assessment of population health provides a different picture than traditional mortality-based assessments. This study demonstrates the feasibility and constraints of using DALYs to assess the burden of disease and injury at the state level.